An analysis of the feasibility of short read sequencing. - Whiteford, N.; Haslam, N.; Weber, G.; Prügel-Bennett, A.; Essex, J.W.; Roach, P.L.; Bradley, M.; Neylon, Cameron (Oxford University Press, 2005)
Several methods for ultra high-throughput DNA sequencing are currently under investigation. Many of these methods yield very short blocks of sequence information (reads). Here we report on an analysis showing the level of genome sequencing possible as a function of read length. It is shown that re-sequencing and de novo sequencing of the majority of a bacterial genome is possible with read lengths of 20-30 nt, and that reads of 50 nt can provide reconstructed contigs (a contiguous fragment of sequence data) of 1000 nt and greater that cover 80% of human chromosome 1.